Engagement, Innovation, and Futures: Strategic Pathways for Applied Research Universities - Rask, Mikko (Rastros Rostros, 2026)
This paper examines how applied research universities can enhance their societal engagement by leveraging global trends in co-creation, knowledge transfer, and institutional innovation. The Universidad Cooperativa de Colombia (UCC) invited this contribution as part of the design process for its new National Strategic Plan (PEN) 2026–2029, the institution-wide strategy that sets priorities across its multicampus system. Responding to this mandate, the paper proposes a thematic framework that connects UCC’s cooperative identity and multicampus presence with international debates on research, innovation, and engagement. Four thematic entry points are developed. Section 2 examines participatory agenda-setting, with a focus on frameworks such as Responsible Research and Innovation (RRI) and foresight methods. Section 3 discusses helix collaboration and co-creation, highlighting how universities convene partnerships across sectors. Section 4 turns to institutionalisation, exploring governance, incentives, and curricular integration of societal engagement. Section 5 addresses digital infrastructures and collective intelligence, emphasising how artificial intelligence and open platforms are reshaping both academic practices and university–society interaction. Each theme is analysed with reference to global trends and illustrated with selected Latin American cases. These examples, presented as sources of inspiration, demonstrate how regional universities are incorporating engagement into their strategic planning, experimenting with citizen science, integrating social responsibility into development plans, and connecting with international open science networks. By juxtaposing such illustrations with UCC’s existing assets — clinics, transfer structures, territorial programmes, and SDG alignment — the analysis offers a comparative lens rather than an institutional diagnosis. The strategic synthesis in Section 6 presents these insights in a matrix that links global practices, Latin American illustrations, and UCC’s current strengths. This comparative approach highlights that UCC is not starting from zero. Instead, it has a robust base of practices that can be made more systematic, better connected across campuses, and more visible in national and international arenas. The paper concludes with nine recommendations, organised under the university’s three main functions: research, teaching, and societal interaction. These recommendations emphasize governance and incentives for research agendas, curricular pathways for project-based learning, and facilitation skills, as well as the role of multicampus networks as civic hubs facilitated by responsible digital infrastructures. By consolidating its cooperative mission and aligning with global benchmarks, UCC can reinforce its leadership in Colombia while contributing to broader international debates on the role of universities in democratic renewal and sustainable development.